Four simple stimuli that induce host‐seeking and blood‐feeding behaviors in two mosquito species, with a clue to DEET's mode of action. Issue 1 (23rd May 2013) - Klun, Jerome A.; Kramer, Matthew; Debboun, Mustapha
ABSTRACT: Bioassays in a wind tunnel showed that a combination of four stimuli releases intense host‐seeking and blood‐feeding behavioral responses from females of the Asian tiger mosquito, Aedes albopictus, and the yellow fever mosquito, Aedes aegypti. The stimuli are carbon dioxide, water vapor, warmth, and adenosine triphosphate (ATP). Mosquitoes responded to this combination with a repertoire of blood‐feeding behaviors that included upwind flight, landing, probing, and engorgement. Absence of carbon dioxide, water vapor, or ATP from the combination of stimuli or exposure to temperatures 12° C below or above human‐host temperature (38° C) significantly attenuated blood‐feeding behavior in both species. Although there is literature documenting the individual importance of each of these stimuli, our work represents the first instance where this combination of stimuli was found sufficient to elicit a complete repertoire of blood‐feeding behaviors in these mosquitoes without involvement of any host specific odor. When mosquitoes were exposed to the four stimuli along with N, N‐diethyl‐3‐methylbenzamide (DEET), feeding behavior was greatly suppressed. We hypothesize that a possible mode of action for DEET against these mosquitoes involves interference of warmth and/or water vapor receptors. An electrophysiological study designed to determine if DEET adversely affects the function of these receptors would be illuminating.